RESOURCE USE EFFICIENCY OF TEMPERATE SILK COCOONS IN NORTH-WESTERN HIMALAYAN REGION OF KASHMIR VALLEY, JAMMU AND KASHMIR, INDIA - Ruyida MUSHTAQ; Tariq Ahmed RAJA; Abida FAYAZ; Harmeet SINGH; Pervez AHMED; Mushtaq Rasool MIR; Rajesh YADAV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Sericulture's resource efficiency are critical for long-term growth and contributes greatly to Kashmir's rural and urban economies for sustainable livelihood and inclusive growth. Mulberry plantations, silkworm rearing, reeling, and silk textile manufacturing is all part of the silk farming process. The primary goal of this research was to determine the socioeconomic features of silk worm rearers, as well as to analyze and assess the resource use pattern of silk cocoon in Kashmir valley. The study is empirical in nature, and data was collected from 334 respondents in silk farming-rich zones such as Anantnag and Baramulla in 2021-22 utilising a pre-tested structured interview schedule and purposeful stratified random sampling. Descriptive statistics and Cobb Douglas production function analysis were used to conduct this study's analysis. The results showed that generally, silk worm rearers in Baramulla and Anantnag were inefficient in their use of resources avail‑able to them. Silkworm seed, mulberry leaves, silkworm rearing sheds were underutilized, while labour, disinfectants were over utilized by the farmers. The results further showed that sericulture farmers in Anantnag and Baramulla exhibit increasing returns to scale, indicating that the famers can increase their output by increasing the use of some of the key resources. The finding revealed that silk rearers in Baramulla and Anantnag districts of Kashmir valley were experiencing increasing return to scale. As the total of calculated coefficients of significant variables was found to be more than unity, (1.32).MVP indicates that there is still scope to invest in the study's elements in order to attain the best resource combination and profit maximisation. Incentives and techniques targeted at encouraging farmers to enhance silk cocoon production, such as better government administration of the current subsidy programme and efficient input delivery through sericulture-based centres to ensure silk worm farmers have easy access. This research proved that an intense integrated approach to balanced regional development can help the Kashmir valley's silk industry survive.